DETERMINAN BELANJA MODAL DAN KONSEKUENSI TERHADAP PENDAPATAN PERKAPITA (STUDI KASUS WILAYAH JAWA TENGAH) - Hardiningsih, Pancawati; Oktaviani, Rachmawati Meita (Proceeding Fakultas Ekonomi, 2013)
This study aimed to determine the effect of fund balance consists of the general allocation funds,  special allocation funds, financial assistance from the Provincial Government. The revenue and capital expenditure allocation to determine the effect of capital expenditures in each district/city in the administrative area of Central Java Provincial. The data used in this study were obtained from various data sources such as data from the district budget/ city, allocation funds transfer from the Directorate General of Fiscal Balance  regional Ministry of Finance of the Republic of Indonesia, Central Bureau of Statistics and Central Java to the research data period of 4 (four) years the Fiscal Year 2008-2011. Hypothesis  test  results  showed  the  general  allocation  funds  and  the  financial  assistance  that significantly affect the allocation of capital expenditures in the district/town in the administrative region of Central Java province, while for components DAK, and revenue does not significantly affect the allocation of  capital expenditure . In this study, capital expenditure budget contained in the distric/city government  administrative region showed a positive effect on per capita income of the area.   Keywords: Balance Fund, Capital Expenditure, Decentralization Fiscal, Per Capita Income